2021
DOI: 10.1007/s00216-021-03781-y
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric approach to quantitative analysis of biomolecules: the case of nucleic acids

Abstract: Majority of protocols for quantitative analysis of biomarkers (including nucleic acids) require calibrations and target standards. In this work, we developed a principle for quantitative analysis that eliminates the need for a standard of a target molecule. The approach is based on stoichiometric reporting. While stoichiometry is a simple and robust analytical platform, its utility toward the analysis of biomolecules is very limited due to the lack of general methodologies for detecting the equivalence point. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…We make the quadruplex assembly contingent on the presence of a target oligonucleotide strand. For the proof-of-concept demonstrations, we derive a target from a rat prolactin promoter sequence (used as a model in ( 46 ) and our prior publications ( 47 , 48 )). We split G-quadruplexes into left (L) and right R ‘arms’ (Figure 3 , domains a and b ) and extend the ‘arms’ with target recognition domains ( c and d ) that are complementary to fragments c’ and d’ on a target.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We make the quadruplex assembly contingent on the presence of a target oligonucleotide strand. For the proof-of-concept demonstrations, we derive a target from a rat prolactin promoter sequence (used as a model in ( 46 ) and our prior publications ( 47 , 48 )). We split G-quadruplexes into left (L) and right R ‘arms’ (Figure 3 , domains a and b ) and extend the ‘arms’ with target recognition domains ( c and d ) that are complementary to fragments c’ and d’ on a target.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we are very enthusiastic about extending the catalase system into a field of quantitative analysis. The target-assembly activatable system (split) is compatible with a stoichiometric approach for quantitative analysis of biomolecules we developed earlier ( 47 , 48 ). We have preliminary demonstrated that the approach enables naked eye quantitative analysis of a target T1 at 500 nM level ( Supplementary Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%